The Effect of Intrapersonal and Interpersonal Intelligence on Mathematics Learning Motivation - Yunni Arnidha; Esti Maulani (Universitas Sarjanawiyata Tamansiswa, 2022)
Learning motivation is an energy that exists within a person to do something by achieving a change in behavior which is characterized by feelings and reactions in the environment to achieve a goal to be achieved. The purpose of this study was to determine the effect of intrapersonal and interpersonal intelligence on students' motivation to learn mathematics in Pringsewu Regency. This type of research uses descriptive quantitative research, using ex post facto research methods. The population in this study were fourth grade students of SD Negeri Cluster 1, Sukoharjo District, which opened 97 students. The data collection technique is using proportional random sampling technique. Researchers took samples using the formula from Taro Yamane and Slovin so that a sample of 78 respondents was obtained. Data analysis using descriptive statistical analysis techniques, and the final analysis (hypothesis testing) using multiple regression test. The results obtained indicate that, there is a significant between intrapersonal intelligence and interpersonal intelligence on the mathematics learning motivation of students in Pringsewu Regency, this is evidenced by the value of Fcount 14,629 >Ftable 3.12, or Ho is rejected and Ha is accepted.